Tabloidyzacja audycji informacyjnych – przyczynek do badań - Ossowski, Szymon (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The text presents and briefly discusses the methodological premises and partial research results of a study fully presented in a book by D. Piontek, B. Hordecki and S. Ossowski Tabloidyzacja dyskursu politycznego w polskich mediach [The tabloidization of political discourse in the Polish media], published by the academic publishing house of the Faculty of Political Science and Journalism of AMU (Poznań 2013). On the basis of the criterion of viewership of Polish channels as well as news programs, the news service Wiadomosci TVP1 and Fakty TVN were selected as the object of the study; the timeframe covered the first two weeks of every month beginning in September 2011 and finishing in August 2012. The research sample amounted to 154 issues of each program. A single news item constituted the object of analysis, while every news item classified as political underwent additional in-depth analysis. A total of 1,421 news items were analyzed (including 350 political ones), 783 from Wiadomosci and 638 from Fakty.